Pendekatan Pembelajaran Abad 21 dalam Meningkatkan Literasi Sejarah dan Karakter Siswa - Septiana, Nabila; Jayan, Aulya Akmal; Faldam, Razin; Safitri, Sani; Oktapiani, Rani (Lembaga Pengembangan Kinerja Dosen, 2025)
This article will explain the usage of 21st-century learning for the improvement of historical literacy and students’ character. History class, according to some students, might be considered boring. That is why an entertaining way to teach history is needed to improve students’ historical literacy and make the learning process more engaging and effective. Good historical literacy not only helps students understand the past but also plays a crucial role in shaping their character based on the values embedded in historical subjects. The method used in this article is qualitative, and the analysis is based on various literature sources related to 21st-century learning approaches. The findings highlight how integrating 21st-century learning strategies such as digital tools, interactive activities, and collaborative learning can transform the history learning process. By making history more engaging and interactive, students are not only able to improve their understanding of historical events but also internalize positive character traits, fostering critical thinking, responsibility, and empathy, all of which are essential for their personal development.